255 PRO-B-TYPE NATRIURETIC PEPTIDE IN ST-ELEVATION MYOCARDIAL INFARCTION: CORRELATION WITH TRADITIONAL MARKERS AND INDICATOR OF LONG-TERM LEFT VENTRICULAR DYSFUNCTION. (1st January 2006) - Godkar, D.; Gupta, A.; Juliard, K.; Niranjan, S.; Cucco, R.; Khanna, A.
Abstract : Background: The circulating peptide, pro-B-type natriuretic peptide (pro-BNP) was examined for prediction of cardiac function and prognosis and compared with previously reported markers [cardiac troponin I (cTnI) and creatine phosphokinase (CPK)] in patients with ST-elevation myocardial infarction (STEMI). Methods and Results: We examined plasma levels of pro-BNP, cTnI, and CPK in 84 patients presenting with STEMI. Patients presenting with KILLIP's class 3 and 4, renal failure, and a previous history of low ejection fraction (EF) were excluded. EF was determined by echocardiography 6 months after STEMI. Of the 84 patients in this study, 60 (71%) were male and 24 (29%) female. Their ages ranged from 43 to 88 yr, with a mean of 63.6 yr (SD 13.0 yr). The correlation between pro-BNP and CPK was excellent (r=.88, p < .001), while the following correlations were on the borderline of fair to moderate: pro- BNP and cTnI (r = .52, p < .001) and cTnI and CPK (r = .50, p < .001). Left ventricular ejection fraction at 6 months was moderately negatively correlated with peak CPK (r = 2.64, p < .001) and pro-BNP (r = 2.66, p < .001); its negative correlation with cTnI (r = 2.47, p < .001) was only fair. Conclusions: We conclude that increased concentrations of pro-BNP at initial presentation of patients with STEMI correlate well with levels of CPK and the may reflect long-term left ventricular dysfunction in these patients. These data support the value of combining markers of hemodynamic stress with traditional approaches to risk assessment in acute myocardial infarction.